Positioning Koperasi Melalui Pendekatan ICA Grid Model: Studi pada Koperasi Peternakan Sapi Bandung Selatan - Dandan Irawan (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2021)
In order to know whether a cooperative organization is really a cooperative in a true sense, it is necessary to first look at its identity. The identity of a cooperative is a basic characteristic inherent in a cooperative since its birth. It undergoes a very long and crystalline process of growth and maturity, thus placing the cooperative as a business entity that has a positioning for its members. Cooperatives operate in a space that is limited by their identity and by the rules that apply to free market players such as corporations. Cooperatives also play in a competitive market economy and also in an environment where market conditions sometimes do not apply. Therefore for cooperatives it is important to know where their position is at certain times in an effort to maintain and secure their identity, with the aim of maintaining their existence as a cooperative.